MENEPIS RATU ADIL SEBAGAI RAMALAN DAN MENGHADIRKAN RATU ADIL SEBAGAI WACANA KEPEMIMPINAN - Minardi, Minardi (JURNAL ISLAM NUSANTARA, 2017)
Ratu Adil means a just leader who leads the just and at the same time spreading the justice. According to Ronggowarsita there will be seven Ratu Adil. It turns out that the first Ratu Adil until the sixth has the criteria that match the first RI president to sixth. The seventh fair is the Satria Pinandhita Sinisihan Wahyu. He is a knight, that is someone who is familiar with the state administration. He is also a religious scholar who walks on the revelations of God. Ratu Adil is only limited to be understood as a prophecy for the coming of a character to bring goodness. This is the problem, should be seen as a concept of national leadership that needs to be realized for the progress of Indonesia. The type of research used in this study is library research (Library Research), where in this study the authors held observations in the library, or where the authors obtain data and information about the object of research either through books or other visual tools. With the people who animate Ratu Adil it will easily lead to a leader who has a spirit of Ratu Adil. While the criteria of Satria Pinandhita Sinisihan Wahyu namely; 1). Satria include: Anggana, anggung, gumulung, Democracy Need Vision or Idealism; 2). Pinandhita Sinisihan Revelation: Eling versus Waspada, Ratu Adil Anggana Raras, Brahmana King's Word